Análisis del manejo de la comunicación institucional que realiza la Coordinación Zonal 7 del Ministerio de Justicia, derechos humanos y cultos, durante el periodo enero-diciembre 2014; y, su incidencia en el conocimiento que tiene la ciudadanía lojana de los servicios que brinda esta entidad - Davila Aguirre, Karen Liliana (2015)
This thesis was conducted in order to analyze the management of institutional communication which takes 7 Zonal Coordination Ministry of Justice, Human Rights and Religious Affairs, located in the city of Loja. To meet this goal the activities and strategies used this institution for the diffusion of his important work on the rights of citizenship and what their weaknesses are identified. The methods used were scientific, analytical method - synthetic, inductive - deductive; and statistical, the same that were used to describe and explain how and relationship that exist in the management of institutional communication. For field research, made a pre Loja citizens and users of the Ministry of Justice survey was conducted. According to the survey of the lojana community, it was established that the spread of service provided by the Coordination MJDHC Zonal 7 to the community is largely unknown, concluding that the MJDHC handles corporate communications in an inappropriate manner, that is to say, without a communication plan, limiting its spread. Based on the assessment made to the Ministry the urgent need to find new ways in communications management, for which a basic communication plan is presented, consisting of the same analysis is outlined, objectives, strategies and tactics of communication, organization presents workshops, and execution, schedule, budget, finance and communication products. Key words: Communication, diffusion, strategy, failures, communication plan.